TEKNOLOGI MICRO ELECTRO MECHANICAL SYSTEMS - Slamet Widodo; Tony Kristiantoro (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
In this paper described the technology Microelectromechanical systems (MEMS) was applied in several fields including biology, chemistry, physics, telecommunications, electronics, medical, defense and so forth. A microelectromechanical system (MEMS) is one of the components (devices) are relatively small (micro scale) consists of components (devices) micromechanical (like microgears, microlevers, etc.), which moves both in response to certain stimuli (sensors) or the initiative to perform certain tasks (actuators), and microelectronic components to obtain information from, or control, or motion. In a broader sense, associated with MEMS technology, including materials and processes required to make MEMS components, integration components to create MEMS devices (sensors, actuators, etc.) and applications that use the devices (device) MEMS. In addition, other microsystems such as microchemical reactors, microthermal systems and smart materials (such as shape memory alloy) are also sometimes included in